Residual strain optimization in 3D MOSFET structures for enhanced mobility via nanoscale heat transfer - Hong, Ji Hoon; Kang, Min Sung; Ha, Inho; Park, Hong Lae; Park, Kyungwook; Jeon, Joohyun; Yoo, Wonseok; Kim, Jueun; Chung, Chunhyung; Park, Sung Min; Cho, Sung Beom (Journal of Applied Physics, 2025)
This study addresses the optimization of strain in continuous MOSFET downscaling, particularly at the nanoscale, where traditional Fourier models fail due to non-diffusive phonon transport effects. We introduce a multi-physics simulation approach that combines Finite Element Method (FEM) and Density Functional Theory (DFT) calculations to design strain-optimized 3D MOSFET structures. By implementing the kinetic collective model within FEM simulations, we accurately predict thermal-induced strains in the Si channel layer. Our DFT calculations further elucidate the impact of these strains on the electronic properties, particularly the electron effective mass, thereby offering insights into mobility enhancement strategies. The study not only advances the implications of nanoscale heat transfer for device performance but also provides a robust framework for optimizing next-generation semiconductor devices through strain engineering and sophisticated multi-physics simulations.
Keywords: Density-functional theory calculations; Element method; Enhanced mobility; MOSFET structures; MOSFETs; Multiphysics simulations; Nanoscale heat transfers; Residual strains; Strain optimization